Causal Factors Of Consumer Loyalty To Online Food Delivery Services Of Delhi ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: The internet-based cuisine transportation industry observed noteworthy expansion, transforming the  approach individuals requested and obtained their repasts. This metamorphosis was propelled by elements such as the  ubiquitous utilization of portable gadgets and the escalating need for expediency in everyday existence. Internet-based  food delivery services gained popularity in Delhi, offering a wide range of culinary options and timely delivery to meet the  needs of customers. Objective: This investigation endeavored to scrutinize the elements that impacted patron allegiance  to web-based cuisine transportation amenities in Delhi and assessed the correlation between client gratification and  faithfulness. Methodology: This study employed hybrid research methodology, gathering qualitative data through a  structured questionnaire (n=50) in the NCR Delhi and secondary data from sources like trade publications, scholarly  journals, and online repositories. Elements Analyzed: Ease of use, Food options quality, Consumer engagement, Delivery  efficiency, Economical pricing, Client support. The quantitative data was analyzed using survey response metrics  and descriptive statistics (mean, median, mode, standard deviation). The analysis involves descriptive examination  of survey responses and correlation analysis for associations. Results: Ease of use: 4.5/5 (Average), Food quality:  85% above satisfactory, Consumer engagement: 70% high, Delivery efficiency: 90% prompt, Pricing: 60% reasonable,  Client support: 80% helpful. The scrutiny furnished perceptions into the factors that influenced customer allegiance  and the correlation amid ease, cost competitiveness, patron contentment, and allegiance. The outcomes were exhibited  employing statistical metrics, association coefficients, and significance levels. Conclusion: The exploration aided  in comprehending the elements that impacted patron fidelity to web-based cuisine conveyance amenities in Delhi. It  emphasized the significance of ease, patron contentment, consumer involvement, punctual dispatch, rivalrous cost, and  efficient patron maintenance in cultivating allegiance.
Keywords: Online Food Delivery; Consumer Loyalty; Customer Satisfaction; Competitive Pricing; Customer Service